2022
DOI: 10.21037/atm-22-1810
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell immune ecosystem and metabolism reprogramming imprinted by psoriasis niche

Abstract: Background A major challenge of psoriasis is its dysfunctional immune niche. Remarkable gaps remain in understanding how immune cell state transitions are linked to clinical outcomes in psoriasis. Thus, there is a pressing need to discover immunomodulatory programs governing psoriasis progression. Methods Here, by using the state-of-the-art single-cell RNA-sequencing (RNA-seq) data, we observed the unique immune cell profile inside the psoriasis niche compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…35,36 Furthermore, recent studies also suggested that metabolic reprogramming is emerging as another crucial regulatory paradigm for psoriasis. [37][38][39] Extracellular cytokine pathways The TNF/IL-23/IL-17 pathway. The findings of a large number of genome-wide association studies (GWAS) and clinical trials support the central role of TNF-IL-23-IL-17 signaling pathways in the pathogenesis of psoriasis, especially for plaque psoriasis.…”
Section: Signaling Pathways Driving Psoriasis Pathogenesismentioning
confidence: 99%
“…35,36 Furthermore, recent studies also suggested that metabolic reprogramming is emerging as another crucial regulatory paradigm for psoriasis. [37][38][39] Extracellular cytokine pathways The TNF/IL-23/IL-17 pathway. The findings of a large number of genome-wide association studies (GWAS) and clinical trials support the central role of TNF-IL-23-IL-17 signaling pathways in the pathogenesis of psoriasis, especially for plaque psoriasis.…”
Section: Signaling Pathways Driving Psoriasis Pathogenesismentioning
confidence: 99%
“…Previous studies addressing TCRβ repertoire diversity in the context of psoriasis have been conducted in whole skin biopsy samples 38 40 , total peripheral mononuclear cells 41 and sorted cutaneous CD4 + T cell effector and regulatory T cells 42 , CD8 + 42 , 43 or CD45 + 44 T lymphocytes, providing little insight into the TCRβ clonotype diversity of MR1-restricted MAIT cells in PV. The MAIT TCR repertoire in healthy donors was most recently examined in single-cell TCRSeq settings, providing evidence for highly private, individually unique MAIT CDR3β sequences in the periphery 18 , while clonally expanded MAIT repertoire was primarily demonstrated in bone marrow, spleen and lungs, but not in healthy skin 45 .…”
Section: Introductionmentioning
confidence: 99%